PENTINGNYA PENDIDIDKAN ANTI KORUPSI SEJAK USIA DINI - Reggie Andrea Adnan; Edy Soesanto, Rendy Rusdiyanto, Agung Listianto (CV. ADIBA AISHA AMIRA, 2024)
This research aims to describe the implementation of anti-corruption education, the application of anti- corruption educational values, the application of anti-corruption educational values by pre-service teachers, teaching students and their relationship with citizenship. The research method used is a descriptive method with a qualitative approach. The data collection techniques used were observation, interviews and notes. Data analysis techniques begin with data collection, data reduction, data presentation, and drawing conclusions. Based on the research results, it can be concluded that the implementation of anti-corruption education in Bekasi City is not optimal, with variable (X) Anti- corruption education of the teaching team, then variable (Y): students. Values in anti-corruption education are closely related to citizen ethics. Anti-corruption education is one of the efforts provided to the community to equip the community with the knowledge, ethical values, attitudes and skills needed to reduce opportunities for committing corruption. In anti-corruption education there are 9 values where the values are the values given by the KPK organization. These nine values include honesty, kindness, responsibility, hard work, independence, simplicity and courage, discipline and fairness. The nine anti- corruption values are related to the values or ethics of citizens which contain norms that exist in society, namely religious norms, social norms, ethical norms and legal norms. Anti-corruption education was born as a study at a higher level and is part of character education for students. This is to produce students who are honest, intelligent, have morals and integrity as the nation's next generation who will guide Indonesia towards goodness. This is also an effort to prevent and reduce the eradication of corruption in Indonesia. Eradicating corruption must be carried out in Indonesia because in this case Indonesia is ranked fifth out of eight ASEAN countries. One of the manifestations of anti-corruption education is implementing anti-corruption values and principles to inhibit the influence of internal and external factors. The aim of this research is to develop students so that they are not affected by acts of corruption by instilling themselves with anti-corruption values and principles. and the method applied in writing this article is descriptive qualitative combined with the application of library study methods